2016
DOI: 10.1002/ppsc.201500170
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Europium(III) from Water using Magnetite Nanoparticles

Abstract: It is demonstrated that colloidal magnetite nanoparticles can be used as nanosorbents for lanthanide ions dissolved in water. In particular, a series of experiments are performed for the removal of Eu(III) in distinct analytical conditions and by applying an external magnet to collect the sorbents previously dispersed in water samples. Furthermore, strategies for surface chemistry functionalization are also investigated, aiming to investigate the effect of this parameter on the removal capacity of the Fe3O4 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 69 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…The application of magnetic nanosorbents for the removal of herbicides remains a less explored area in the context of water purification. Our research group has reported a range of magnetic nanosorbents that are effective for the removal of distinct water pollutants, using magnetically-assisted procedures [ 26 , 27 , 28 , 29 , 30 , 31 ]. In particular, nanosorbents composed of magnetic cores and biopolymers at the surface are promising candidates for the removal of certain emerging organic pollutants from water, using magnetically-assisted technologies [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of magnetic nanosorbents for the removal of herbicides remains a less explored area in the context of water purification. Our research group has reported a range of magnetic nanosorbents that are effective for the removal of distinct water pollutants, using magnetically-assisted procedures [ 26 , 27 , 28 , 29 , 30 , 31 ]. In particular, nanosorbents composed of magnetic cores and biopolymers at the surface are promising candidates for the removal of certain emerging organic pollutants from water, using magnetically-assisted technologies [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fate of Ce­(III) during the preparation of GR and magnetite from preformed ferrihydrite has been investigated by Nedel et al Ce­(III) initially retained by ferrihydrite was only partially released upon phase transformation to magnetite but was quantitatively released upon transformation of ferrihydrite to GR. Separately, studies indicate that preformed magnetite has a high affinity for sorption of Ln­(III). However, no study reported structural data by directly probing the retained Ln­(III) species.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison study of Eu( iii ) adsorption was conducted with four different types of magnetic adsorbent materials including bare magnetite (Fe 3 O 4 ), silica-coated magnetite (Fe 3 O 4 @SiO 2 ), and silica-coated magnetite with surfaces functionalized with amine groups (Fe 3 O 4 @SiO 2 /APMS) and dithiocarbamate groups (Fe 3 O 4 @SiO 2 /DTC). 42 As a result of subsequent modification, the net surface charge was significantly varied from 2.2 to −44 mV. These materials adsorbed Eu in the order of Fe 3 O 4 @SiO 2 ≈ Fe 3 O 4 @SiO 2 /APMS > Fe 3 O 4 > Fe 3 O 4 @SiO 2 /DTC at pH 7 in DI water; higher adsorption was due to the preferred coordination of Eu( iii ) with the O donors.…”
Section: Classification Of Magnetite-based Adsorbentsmentioning
confidence: 94%
“…Silica coating can be achieved through Stober process via sol-gel reaction which involves the use of tetraethyl orthosilicate (TEOS) in acidic and/or basic pH conditions under vacuum. Several works have been reported in the literatures demonstrating the effective use of silica protected m-NPs graed with various functional groups for the removal of radionuclides, 42,44 . However, the -Si-O-Si-bond in silica coating is susceptible to rapid degradation in basic conditions resulting in signicant loss of surface-graed functional groups.…”
mentioning
confidence: 99%